The Effect of Duolingo Application on Student’s English Vocabulary Mastery at Tenth Grade Student of SMA N 11 Jambi City - Suyadi, Suyadi; Silfia, Efa; Haris, Fhilhamdhi Al (Universitas Batanghari Jambi, 2024)
The main problem of this research are the Understanding and Mastering English Vocabulary of student while learning, especialy at school. The aim of this study is to find the student capabilities and the determination of student in Vocabulary, especialy in the absent of class directly at school while Covid-19 Lockdown few years back. The researcher will use field research as a method of inquiry, observation and survey aswell. Research participants are 52 students who’s In Tenth Grade. From these, the finding are most of the student had a problem with the Environment or Surrounding of their learning area, while the rest had a problem with the Learning progress. Based on these, the Student had a trouble in learning while at school because their classmate, the task from other subject, and short hour to study English in class or while at home because of their homework from other subject, helping chores around the house as well as they need some breaktime from school since morning. Even more so while on Covid-19 few years back these student had to study at their home and most of the time the teacher explaining the materiel for a bit before throwing a homework or task for them to do. And while studying process it’s not effective example like because of the lack of direct communication, noisy surrounding, not enough sufficient device for said learning class, and the list still going on. As the result those years of direct learning and leap of class, carried away until they are now in Tenth Grade. Especialy the student that just started learning or not proficient in English had a trouble at learning English Langguage in GeneralKeywords: Capabilities and Determination, Environment, Surroundings, Learning, Communication